2018
DOI: 10.1021/acs.joc.8b00586
|View full text |Cite
|
Sign up to set email alerts
|

Access to β2-Amino Acids via Enantioselective 1,4-Arylation of β-Nitroacrylates Catalyzed by Chiral Rhodium Catalysts

Abstract: The highly enantioselective conjugate addition of a variety of arylboronic acids to β-nitroacrylates is reported to provide optically active α-aryl β-nitropropionates in up to 70% yields and >99.5% ee's, which are useful building blocks for preparing chiral β-amino acids. The applicability of this transformation is demonstrated by converting 3aa into the β-amino acid 5 and transforming 3ap to β-amino ester 7 via reduction and reductive N-alkylation. The latter compound is a precursor for preparing ent-ipataser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 78 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Wu further studied a similar transformation and in 2018 reported a Rh‐catalyzed conjugate addition of arylboronic acids to β‐nitroacrylate 21 (Scheme ) . Both electron donating and withdrawing substituents on the aromatic ring were tolerated, and β 2 ‐arylglycine analogues 22 were generally obtained in moderate to good yields with excellent enantioselectivities.…”
Section: C(α)–h/r Bond Formationmentioning
confidence: 99%
“…Wu further studied a similar transformation and in 2018 reported a Rh‐catalyzed conjugate addition of arylboronic acids to β‐nitroacrylate 21 (Scheme ) . Both electron donating and withdrawing substituents on the aromatic ring were tolerated, and β 2 ‐arylglycine analogues 22 were generally obtained in moderate to good yields with excellent enantioselectivities.…”
Section: C(α)–h/r Bond Formationmentioning
confidence: 99%
“…N -Acyliminium ions (NAIs), as highly reactive electrophiles and important building blocks, have been widely used in organic and pharmaceutical synthesis. 1 Over the past decades, a large number of reports described the addition process of various nucleophiles to NAIs, and such methods have been widely used in the synthesis of alkaloids, 2 natural-product-like substances, 3 pharmaceuticals, 4 and biologically active compounds. 5 Three general approaches were often used for the preparation of NAIs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 In numerous syntheses, it has been used as a catalyst for cyclopropanation, 5 , 6 hydroformylation, 7 , 8 and C–H bond activation; 9 , 10 what is more, it has also been used for manufacturing acetic acid 11 and β2-amino acid. 12 In particular, Shan et al 13 reported a mononuclear rhodium species, which was anchored on a zeolite or titanium dioxide support suspended in an aqueous solution; they catalyzed the direct conversion of methane to methanol and acetic acid using oxygen and carbon monoxide under mild conditions. Furthermore, they proposed that the conversion of methane to oxygenate occurred via an activation in the presence of O 2 on isolated Rh + cations; this was observed under mild conditions, which led to the production of Rh–CH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Rh is regarded as an important active center, which is widely applied in various syntheses and their catalysis. In numerous syntheses, it has been used as a catalyst for cyclopropanation, , hydroformylation, , and C–H bond activation; , what is more, it has also been used for manufacturing acetic acid and β2-amino acid . In particular, Shan et al reported a mononuclear rhodium species, which was anchored on a zeolite or titanium dioxide support suspended in an aqueous solution; they catalyzed the direct conversion of methane to methanol and acetic acid using oxygen and carbon monoxide under mild conditions.…”
Section: Introductionmentioning
confidence: 99%